Effect of citric acid on extracellular polymeric substances disruption and cell lysis in the waste activated sludge by pH regulation. (April 2020) - Wu, Xuewei; Li, Xiaoming; Yang, Qi; Xu, Qiuxiang; Tao, Ziletao; Huang, Xiaoding; Wu, You; Tao, Lingjuan; Pi, Zhoujie; Chen, Zhuo; Wang, Dongbo
Graphical abstract: Highlights: CA pretreatment at an acidic environment could result in outer EPS destruction accompanied by cell lysis. CA pretreatment could improve sludge dewatering degree but could not increase sludge dewatering speed. CA have deflocculation property which could influence EPS removal and cell lysis promotion. Help to understand the use and promotion of CA in practical applications. Abstract: This paper investigated the effects of citric acid (CA) on extracellular polymer destruction and cell lysis in sludge at different initial pH by measuring capillary suction time (CST), extracellular polymeric substances (EPS) and intracellular bound water. The results indicated that under CA concentration at 0.05 g/g suspended solids (SS) and initial pH 4, the CST value decreased from 175.5 s to 112.3 s, slime extracellular polymeric substances (S-EPS) and loosely bound EPS (LB-EPS) content respectively to increase from 4.92 to 41.43, 2.27 to 5.49 mg/g volatile suspended solids (Vss), while tightly bound EPS (TB-EPS) content to decrease from 12.35 to 5.01 mg/g (Vss), which suggested CA could disrupt outer EPS effectively. Intracellular bound water content decreased from 1.23 g/g to 0.41 g/g dry solid (DS). As a result, CA could release intracellular bound water effectively, thereby improving sludge dewatering degree.